Digitizing freeways: researching urban resources - Bredella, Nathalie; Lahusen, Katrin (Enquiry The ARCC Journal for Architectural Research, 2008)
At the beginning of his study on Los Angeles Los Angeles: The Architecture of Four EcologiesReyner Banham writes " ... like earlier generations of English intellectuals who taught themselvesItalian in order to read Dante in the original, I learned to drive in order to read Los Angeles in theoriginal (Banham 1971:23).” Banham implies, that Los Angeles can only be experienced whiledriving. The metropolis, the ‘urban sprawl', cannot be experienced walking but only through thecar. ‘Autopia' became one of the ‘Four Ecologies' of Los Angeles and he states that the ‘automotiveexperience' "prints itself deeply on the conscious mind and unthinking reflexes (ibid.:214).”Cees Nooteboom draws upon this image of the city in his essay " ‘Autopia'(1973) and Passagesfrom ‘The Language of Images'(1987)” and writes about the character of Los Angeles: "Itis, if one can say this, a ‘moving' city, not only a city that moves itself – breaks itself down, buildsitself up again, displaces and regroups itself – but also a city in which movement, freedom ofmovement, is a strong premise of life (Nooteboom 2001:15).” Nooteboom continues how theeveryday live depends upon the system of the road. The constant Movement of the city repeatsitself: "The other cars are mirror images of you in your car. You are driving behind yourself andin front of yourself, next to yourself and opposite yourself, you are the taillights of the one in frontof you. Everything is on the move (ibid.:21).”